2018
DOI: 10.1186/s12879-018-3534-6
|View full text |Cite
|
Sign up to set email alerts
|

Small-area spatial statistical analysis of malaria clusters and hotspots in Cameroon;2000–2015

Abstract: BackgroundMalaria prevalence in Cameroon is a major public health problem both at the regional and urban-rural geographic scale. In 2016, an estimated 1.6 million confirmed cases, and 18,738 cases were reported in health facilities and communities respectively, with about 8000 estimated deaths. Several studies have estimated malaria prevalence in Cameroon using the analytical techniques at the regional scale. We aimed at identifying malaria clusters and hotspots at the urban-rural geographic scale from the Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 31 publications
4
54
0
Order By: Relevance
“…Studies on the association of environmental factors with malaria cases in Cameroon have been illustrated (28,42). In this study, we demonstrated the ability of the GWR technique as a facilitatory tool to understand the spatial interaction of environmental factors with malaria hotspots.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Studies on the association of environmental factors with malaria cases in Cameroon have been illustrated (28,42). In this study, we demonstrated the ability of the GWR technique as a facilitatory tool to understand the spatial interaction of environmental factors with malaria hotspots.…”
Section: Discussionmentioning
confidence: 74%
“…Data for this study was obtained from the demographic and health survey (DHS) program website (https://dhsprogram.com) funded by the United States Agency for International Developments (USAID) following a written administrative clearance (30). The DHS program has been described elsewhere (28). Households are grouped as either an urban (city block or apartment building) or rural (village or group of villages) cluster points (figure 1) and displaced a distance up to 2 km for urbancity clusters and 5 km for rural clusters due to confidentiality.…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Data for this study was obtained from the demographic and health survey (DHS) program website (https://dhsprogram.com) funded by the United States Agency for International Developments (USAIDS) following a written administrative clearance (28). The DHS program has been described elsewhere (26). Households are grouped as either an urban(city block or apartment building) or rural (village or group of villages) cluster points and displaced a distance up to 2 km for urban-city clusters and 5 km for rural clusters due to confidentiality.…”
Section: Data Sourcementioning
confidence: 99%
“…Knowing the spatial variation between malaria cases and environmental factors will aid in targeted funding and resource allocations, prevention programs such as insecticide-treated nets (ITN) distribution, clinical diagnosis, and treatments. The specific objective of this study is to identify ITN coverage in Cameroon and to find the spatial variability between malaria hotspot cases (26) and environmental predictors using the GWR spatial modelling technique.…”
Section: Introductionmentioning
confidence: 99%